2021
DOI: 10.1186/s12931-021-01842-5
|View full text |Cite|
|
Sign up to set email alerts
|

Association between circulating alpha-1 antitrypsin polymers and lung and liver disease

Abstract: Background Alpha-1 antitrypsin deficiency (AATD) is considered one of the most common genetic diseases and is characterised by the misfolding and polymerisation of the alpha-1 antitrypsin (AAT) protein within hepatocytes. The relevance of circulating polymers (CP) of AAT in the pathogenesis of lung and liver disease is not completely understood. Therefore, the main objective of our study was to determine whether there is an association between the levels of CP of AAT and the severity of lung an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Consistent with the clinical observations that serum polymer level can be used as a biomarker for liver disease 71,72 , the measured secreted polymer is strongly correlated with intracellular polymer for all the variants in both vehicle DMSO control (Supplementary Fig. 8b, left panel; Pearson's r = 0.92, P = 4.3 × 10 −31 ) and PU-WS13 treatment condition (Supplementary Fig.…”
Section: Managing the N-terminal To C-terminal Covariance Folding Of ...supporting
confidence: 83%
See 2 more Smart Citations
“…Consistent with the clinical observations that serum polymer level can be used as a biomarker for liver disease 71,72 , the measured secreted polymer is strongly correlated with intracellular polymer for all the variants in both vehicle DMSO control (Supplementary Fig. 8b, left panel; Pearson's r = 0.92, P = 4.3 × 10 −31 ) and PU-WS13 treatment condition (Supplementary Fig.…”
Section: Managing the N-terminal To C-terminal Covariance Folding Of ...supporting
confidence: 83%
“…8a). These results suggest that PU-WS13 has a broad impact on the AAT fold to decrease the polymer pools for around a half of the polymerogenic AAT variants, a metric highly relevant to monitoring liver disease in the patient population 32,[70][71][72] .…”
Section: Managing the N-terminal To C-terminal Covariance Folding Of ...mentioning
confidence: 90%
See 1 more Smart Citation
“…f p < 0.05 for comparison between the groups "Impaired FEV1(%) and normal PFTs" with healthy controls [35]. Some studies have suggested that there is a relationship between increased markers of systemic inflammation and the severity of lung and liver disease [36][37][38]. In our PI*ZZ patients, markers of systemic inflammation, such as increased neutrophils and platelets, were associated with more impaired FEV1(%), but this association was not observed in augmented patients.…”
Section: Variablesmentioning
confidence: 99%
“…A deficiency of functional AAT disrupts the protease-antiprotease balance in the lung, triggering emphysema and COPD 14 . Polymers of AAT are also found to be secreted from liver and lung cells [15][16][17][18][19][20][21] that potentially contribute to inflammation and lung damage [22][23][24] . Compared with efforts focused on Z-AAT, the impact of the many other variants are poorly studied or completely unknown 3,5,7 .…”
mentioning
confidence: 99%